Pemodelan Machine Learning : Analisis Sentimen Masyarakat Terhadap Kebijakan PPKM Menggunakan Data Twitter - Syafrial Fachri Pane; Jenly Ramdan (Jurnal Sistem Cerdas, 2022)
Abstract— In this pandemic era, the government is forced to implement policies that can reduce the daily positive rate of COVID-19. One of these policies is known as PPKM. It is unclear when the pandemic will end, causing data phenomena to be scattered on social media, one of which is Twitter. Therefore, in this study, we conducted an analysis of sentiment originating from tweets from Twitter social media users in the Jakarta area regarding the government's policy, namely PPKM in the face of the COVID-19 pandemic. In this research, we use a Machine Learning approach, namely LSTM. This modeling produces a classification of positive and negative sentiments. The dataset used is 3000 tweets with a time period of September - November 2021. At the preprocessing stage, the data that are ready to be used for modeling are 2176. The results of this study get an accuracy of 0.943. So the model that we propose, namely LSTM, has succeeded in classifying a satisfactory sentiment with a positive number of 92% and a negative 8% of 2176 sentiments, so it can be concluded that the PPKM policy implemented by the Indonesian government in the DKI Jakarta area is said to be effective or positive.